Analisis Efisiensi Biaya Tenaga Kerja Langsung pada PT. Davincy Airindo - Valentina Monoarfa; Lina Putri Taufik; Kartika Putri Husain (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was conducted with the aim to determine the efficiency of direct labor costs carried out by the company PT Davincy Airindo. In this study using literature review and observation, namely by conducting research in the field through direct interviews and data collection, related documents from the company through internet media. The data obtained is analyzed using the quantitative descriptive analysis method, namely how to compare labor costs that actually occur (actual). The results of the analysis will show whether direct labor costs are used efficiently to produce a product. This shows that Direct Labor Cost Control is in the efficient and stable category (in control).